2020
DOI: 10.3390/md18040220
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Induces Apoptosis of HT-29 Cells via the Activation of DR4 and Mitochondrial Pathway

Abstract: Fucoidan has a variety of pharmacological activities, but the understanding of the mechanism of fucoidan-induced apoptosis of colorectal cancer cells remains limited. The results of the present study demonstrated that the JNK signaling pathway is involved in the activation of apoptosis in colorectal cancer-derived HT-29 cells, and fucoidan induces apoptosis by activation of the DR4 at the transcriptional and protein levels. The survival rate of HT-29 cells was approximately 40% in the presence of 800 μg/mL of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Fucoidan has significant antiproliferative effects on a variety of tumor cells. Many studies have indicated that fucoidan binds to a variety of receptors on the surface of the cell membrane and causes apoptosis of tumor cells by activating the endogenous (mitochondrial and endoplasmic reticulum pathway) and exogenous (death receptor pathway) signaling pathways [129,130]. Moreover, Atashrazm et al also found that fucoidan could enhance the ability of natural killer (NK) cells and T cells to kill tumors via activating the immune system and promoting the production of interferon gamma [131].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Fucoidan has significant antiproliferative effects on a variety of tumor cells. Many studies have indicated that fucoidan binds to a variety of receptors on the surface of the cell membrane and causes apoptosis of tumor cells by activating the endogenous (mitochondrial and endoplasmic reticulum pathway) and exogenous (death receptor pathway) signaling pathways [129,130]. Moreover, Atashrazm et al also found that fucoidan could enhance the ability of natural killer (NK) cells and T cells to kill tumors via activating the immune system and promoting the production of interferon gamma [131].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…These polysaccharides are used for various purposes especially in the food-processing industry, medicine, and biotechnology (Giavasis, 2014). Several previous studies suggested that fucoidan exerts the growth and proliferation inhibition in human cancer cells via apoptotic induction (Bai et al, 2020;Blaszczak et al, 2018;Chantree et al, 2020;Deepika et al, 2019;He et al, 2019;Liu et al, 2020;Narayani et al, 2019;Palanisamy et al, 2018). Moreover, some studies reported the effect of fucoidan in suppressing the invasion (Lin et al, 2017) and metastasis (Alekseyenko et al, 2007) of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one of the important bioactivities of fucoidans is an anticancer effect. Two articles in the Special Issue published anticancer activities of fucoidan via inducing apoptosis of cancer cells [ 19 , 20 ]. M. E. Reyes et al reviewed brown seaweed fucoidan in cancer, in particular introduced implications in metastasis and drug resistance [ 21 ].…”
Section: Important Bioactivitiesmentioning
confidence: 99%